Smart Mobile Application for Heavy Equipment Rental - Tobias, Neec Chander (PT. Lentera Ilmu Publisher, 2025)
This study explores the development of an Android-based heavy equipment rental application tailored for PT. Gajah Unggul Internasional. It highlights the pivotal role of information systems in the heavy equipment rental sector, focusing on the specific needs of PT. Gajah Unggul Internasional, a provider of various construction and industrial equipment. To address the demand for a streamlined system to manage borrowing, returning, and restocking equipment, the study proposes an Android application built with the Ionic Framework, a robust open-source SDK. The methodology employs a comprehensive five-stage research design: data collection, inception, elaboration, construction, and transition. The results and discussion section offers an in-depth evaluation of the application, presenting critical components such as use case diagrams, activity diagrams, sequence diagrams, class diagrams, and the system interface. Functionality and efficiency are validated through black box testing, confirming the system's reliability in processes such as login, registration, equipment data access, and rental history tracking. In conclusion, the study demonstrates the successful application of the Ionic Framework to enhance heavy equipment rental operations at PT. Gajah Unggul Internasional. The user-friendly application caters to various stakeholders, emphasizing practicality and efficiency. The article provides valuable insights into leveraging technology to optimize business processes within the heavy equipment rental industry.